The Role of Social Media in Shaping Political Behavior among University Students in Makassar - Azzahra, Mira Riyanti; Rina (Mahogany Journal De Social, 2025)
In the digital transformation era, social media has become a key arena for political communication and participation, especially among youth. Platforms such as Instagram, TikTok, WhatsApp, and X enable rapid and interactive exchanges that shape political awareness and engagement. This study explores the role of social media in influencing the political behavior of university students in Makassar, a city known for its educational and political diversity. Using a mixed-method design, data were collected through surveys of 200 students and in-depth interviews with 20 participants. The analysis employed frequency distribution and thematic interpretation, supported by triangulation for validity. Findings show that 70% of students use social media more than three hours daily, primarily on Instagram and TikTok. These platforms enhance political awareness (70%) and peer discussions (60%), though their impact on political trust is inconsistent. Participation often takes the form of online activism, such as sharing political content (60%) and signing digital petitions (40%), with some extending engagement to voting and rallies. Overall, social media acts as both an empowering and challenging space for democratic participation, highlighting the need for stronger digital literacy to counter misinformation and superficial activism.